2021
DOI: 10.1080/17517575.2021.1924864
|View full text |Cite
|
Sign up to set email alerts
|

A study of KOL effectiveness on brand image of skincare products

Abstract: A study of KOL effectiveness on brand image of skincare productsWith the prevalence of social media that promote interactivity among people, more organizations nowadays have switched their marketing strategies from traditional media to social media. Moreover, they rely on Key Opinion Leader (KOL) to interact with potential customers in various social media for brand building. This paper presents a study exploring how KOL's characteristics affect the KOL effectiveness and the outcome of brand image building of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 58 publications
0
33
0
7
Order By: Relevance
“…In addition, Alshad Ahmad's content also gives the impression of authenticity, which is reflected in his content that shows his closeness to his wild pet animals. This activity eventually has the potential to build a parasocial relationship between Alshad Ahmad and his audience, which in turn affects his popularity and the trust he gains from his audience (Jin et al, 2021;Pöyry et al, 2019;Reinikainen et al, 2020;Xiong et al, 2021). (Myers, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Alshad Ahmad's content also gives the impression of authenticity, which is reflected in his content that shows his closeness to his wild pet animals. This activity eventually has the potential to build a parasocial relationship between Alshad Ahmad and his audience, which in turn affects his popularity and the trust he gains from his audience (Jin et al, 2021;Pöyry et al, 2019;Reinikainen et al, 2020;Xiong et al, 2021). (Myers, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to rigorously obtain the characteristics of KOL, our research summarizes the common characteristics of opinion leaders, live streamers, and celebrity endorsers in existing studies as shown in Table 1 . Xiong et al [ 120 ], and Xu et al [ 122 ] categorized KOL characteristics into attractiveness, trustworthiness, and expertise, which are also common characteristics of opinion leaders, live streamers, and celebrity endorsers, thus our research considers attractiveness, trustworthiness, and expertise as the characteristics of KOL.…”
Section: Theoretical Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…In this background, the key opinion leader (KOL) plays a significant role in increasing product sales by providing a comprehensive evaluation of the product based on real use experience and expertise in product. Consequently, this improves trust levels among consumers, who believed that KOL’s recommendations are more likely to be accepted [ 120 ]. According to statistics, the product sales of top live streamers in Taobao reached 18.905 billion yuan, which accounted for almost 31.7% of the total sales during the 2021 “double eleven” online shopping festival [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He believes that opinion leaders provide information to others and influence their behavior, and they are a bridge between two levels of information dissemination [9]. Unlike traditional celebrity endorsement marketing methods, opinion leaders will interact with potential customers and share their product experience [10].…”
Section: Introductionmentioning
confidence: 99%